THE ADVENTURE OF THE IMAGE THROUGH THE CONFLICT OF INTERPRETATIONS - ARIEȘAN, Ramona Nicoleta (Studia Universitatis Babeș-Bolyai Philosophia, 2019)
The Adventure of the Image Through the Conflict of Interpretations. Starting from the self-image, through the image adventure landscape seen as an ensemble of conflict of interpretation, not only from a single glance or direction, whether it is evasive or complex, we follow our decipherment and transformation, be it process or state. Through multiple hypostases, whether isolated or open, I will focus on certain details that will be addressed as a dimension by means of text or material reproduction, or through the passage of the same image we face each time through the filter of our own existence. We stop the other or ourselves against the other, thus removing the observer or viewer, thus providing not only distinct perspectives on the same subject or the same situation or even the same consequences, but also giving him the opportunity to choose how to relate to the internal and external environment, thus convincing that, to a lesser extent, or greater, he is the one who drives everything. This approach is based not only on the adventure of self-image in the archive of own experiences but also from the outside, from the archive of common experiences perceived by other people.